Perkembangan Pendidikan Islam di Daerah Minoritas Muslim - Nasrul Fauzi; Asep Abdul Muhidin (Pascasarjana IAIN Sorong, 2021)
This study aims to see the existence and description of the development of Formal Madrasahs in the Muslim minority area of ​​Papua (Sorong City). The research method used is qualitative. This study shows that the development of formal Islamic education in Papua is experiencing very rapid development. According to data from the Ministry of Religion of the City of Sorong, until the end of 2021, the number of madrasas starting from the RA to MA levels is 35 units and 1 Islamic college (IAIN Sorong). The number of madrasas spread throughout the city of Sorong helps achieve equal distribution of education, especially in obtaining Islamic education. The result is that the Muslim community can take education with Islamic characteristics freely, starting from the RA level to the tertiary level, so it can be said that Islamic education participates in the progress of Islam in Papua, especially in the field of formal education.